Factors Affecting the Synthesis of Cellobiose Lipids by Sporisorium scitamineum - Oraby, Amira; Werner, Nicole; Sungur, Zehra; Zibek, Susanne (Frontiers in Bioengineering and Biotechnology, 2020)
Cellobiose lipids (CL) are extracellular glycolipids that are produced by many microorganisms from the family Ustilaginaceae. The sugarcane smut fungus Sporisorium scitamineum has been long known as a producer of the glycolipids mannosylerythritol lipids and was recently described to additionally secrete CL as a byproduct. In fact, we identified 11 homologous genes in S. scitamineum by in-silico analysis sharing a high similarity to the CL biosynthesis gene cluster of Ustilago maydis. We here report the first systematic cultivation of S. scitamineum targeting the synthesis of CL with high product titers and its transfer to the bioreactor. In an initial screening we examined different fermentation media compositions, consisting of a mineral salts solution with vitamins and/or trace elements, three carbon sources (glucose, fructose, sucrose), three pH values (2.5, 4.0, 6.7) and three levels of C/N values (42.2 molC·molN-1, 83.8 molC·molN-1, 167.2 molC·molN-1) with urea as nitrogen source. A pH of 2.5 proved to result in the highest product titers. An increase of urea concentration from 0.6 to 1.2 g·L-1 had a positive effect on biomass formation, however the glycolipid formation was favored at a C/N ratio of 83.8 molC·molN-1, using 0.6 g·L-1 urea. Amongst the examined carbon sources, sucrose resulted in an increase in the secretion of cellobiose lipids, compared to glucose. Comparing different media compositions, vitamins were identified as not necessary for CL synthesis. We obtained a concentration of cellobiose lipids of 8.3±1.0 g·L-1 in shaking flasks. This increased to 17.6 g·L-1 in the 1 L bioreactor with additional feeding of carbon source, with a final purity of 85-93 %. As a side product, erythritol and mannosylerythritol lipids were also synthesized. Via HPTLC coupled MALDI-TOF MS we were able to analyse the secreted CL structures. S. scitamineum produces a mixture of acylated low molecular weight D-glucolipids, linked to a 2,15,16-trihydroxy-hexadecanoic acid via their ω-hydroxyl group (CL-B). The produced cellobiose lipids precipitate as needle like crystals at an acidic pH value of 2.5.